KEBIJAKAN LITERASI UNTUK MENINGKATKAN PRODUKTIVITAS PUBLIKASI DI PERGURUAN TINGGI - Mohammad Yamin (JAS-PT (Jurnal Analisis Sistem Pendidikan Tinggi Indonesia), 2018)
This research studies the importance of literacy as an integral part of building a higher education institution through upholding the academic culture. This study is a policy study that analyzes the act of higher education, technology, and research No. 20/2017. This study deals with the need for universities to encourage every lecturer to revive the academic atmosphere and one of them is a scientific publication as the manifestation of the three tasks of higher education. It means that when the academic atmosphere of publication is formed well, it can encourage lecturers to write the scientific publications. Keywords: literacy policy, scientific publication, and three tasks of higher education